RESPONSE TO SELECTION FOR BODY WEIGHT IN THE THIRD GENERATION OF MASS SELECTION OF THE AFRICAN CATFISH (Clarias gariepinus) AT RESEARCH INSTITUTE FOR FISH BREEDING SUKAMANDI - Bambang Iswanto; Imron Imron; Huria Marnis; Rommy Suprapto (Indonesian Aquaculture Journal, 2016)
Genetic improvement of the African catfish (Clarias gariepinus) in Indonesia for increasing growth performance has been conducted by Research Institute for Fish Breeding at Sukamandi through mass selection. Collection and characterizations of the founder populations, building the synthetic base population, first generation and second generation through mass selection were conducted during 2010-2013. Later, in 2014 it was followed by building the third generation. The present study aimed to find out the genetic gain in the third generation in term of response to selection for body weight. Fifty-two pairs of the selected (fast growing) individuals from the second generation were mated to produce the third generation. As a comparison, five pairs of average-sized individuals were mated to produce the control population, as a second generation representative. Larval rearing, nursery and grow-out phases were respectively held for 25 days in the aquaria, 30 days in the concrete ponds and 60 days in the concrete ponds. At the end of each phase, individual samplings of body weight were undertaken. The results showed that mean body weight of the third generation was higher than that of control population at the end of larval rearing phase (0.21 ± 0.26 g versus 0.20 ± 0.15 g), nursery phase (6.12 ± 2.93 g versus 5.80 ± 3.50 g) and grow-out phase (198.67 ± 82.82 g versus 165.22 ± 71.09 g). Those results revealed that response to selection for body weight of the third generation was positive, i.e. about 20.24% (33.45 g).